GIS-Based Evaluation of Flexible Pavement Condition in Kediri Using Surface Distress Index Method - Maulana Zidan Dwi Cahya; Hendrata Wibisana; Aulia Dewi Fatikasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Road infrastructure is a vital component in supporting regional economic growth and social connectivity, including the Gayam–Sidorejo road section in Kediri District, which functions as a primary collector road. This study aims to identify pavement distress along the 8.383 km Gayam–Sidorejo road segment, determine its functional condition using the Surface Distress Index (SDI) method, and visualize the spatial distribution of the distress through Geographic Information System (GIS) mapping. The methodology involved primary data collection through field visual surveys to identify distress parameters, including crack area, crack width, number of potholes, and rutting depth, in accordance with the guidelines of the Directorate General of Bina Marga. These data were then integrated into a spatial database using ArcGIS software to produce thematic maps of road conditions. The evaluation results show that the SDI values for the Gayam–Sidorejo road section range from 10 to 45. The lowest SDI value of 10 was recorded at STA 2+000–2+500, while the highest value of 45 was found at several locations, including STA 1+000–1+500 and STA 8+000–8+383. Based on the analysis, all road segments are classified in